2005
DOI: 10.1002/ppul.20273
|View full text |Cite
|
Sign up to set email alerts
|

Teenage asthma after severe early childhood wheezing: An 11‐year prospective follow‐up

Abstract: The role of factors related to early wheezing and their associations with subsequent development of asthma are controversial. We reevaluated 81 children who had been prospectively followed up since hospitalization for wheezing at less than 2 years of age. The baseline data on characteristics of the children, family-related factors, and viral causes of wheezing were collected on entry into the study. At the median age of 12.3 years, current symptoms suggestive of asthma and allergy were recorded. As part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 32 publications
8
140
3
1
Order By: Relevance
“…For example, a case control study conducted in Finland demonstrated that infants hospitalized with HRV-induced wheezing were found to have a particularly high risk for subsequent asthma, and this relationship persisted at least through the teen years (37,56). This finding is further supported by the results of two birth cohort studies.…”
Section: Hrv As a Lower Airway Pathogensupporting
confidence: 70%
“…For example, a case control study conducted in Finland demonstrated that infants hospitalized with HRV-induced wheezing were found to have a particularly high risk for subsequent asthma, and this relationship persisted at least through the teen years (37,56). This finding is further supported by the results of two birth cohort studies.…”
Section: Hrv As a Lower Airway Pathogensupporting
confidence: 70%
“…Unfortunately, objective evaluation of viral infections on swabs was not available in the MAS. Other studies have found direct evidence of respiratory syncytical virus and rhinovirus infection in infancy to be associated with persistence of asthma in teenagers [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Factors underlying the frequency and severity of episodes are only partially understood, but the severity of the first episode (which is, in turn, related to pre-existent impaired lung function and younger age), atopy, prematurity and exposure to tobacco smoke have been implicated [29][30][31][32][33][34][35]. Whether or not [36][37][38].…”
Section: Definitionsmentioning
confidence: 99%